Designing a thiol specific fluorescent probe for possible use as a reagent for intracellular detection and estimation in blood serum: kinetic analysis to probe the role of intramolecular hydrogen bonding - Das, Priyadip; Mandal, Amal Kumar; Reddy, Upendar G.; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Organic & Biomolecular Chemistry, 2013)
A new and simple chemodosimetric probe L-1 is utilized for the selective detection of biothiols in the presence of other relevant amino acids under physiological conditions (pH = 7.4). This eventually led to a turn-off luminescence response due to an effective photoinduced electron transfer based signaling mechanism. A comparison of the results of the fluorescence kinetic analysis and H-1 NMR studies of the reaction between thiol and L-1 or the analogous compound L-2 revealed the role of intramolecular hydrogen bonding in activating the imine functionality towards nucleophilic addition. Such an example is not common in contemporary literature. Conventional MTT assay studies revealed that this probe (L-1) has low cytotoxicity. Results of the cell imaging studies revealed that this probe was cell membrane permeable and could detect the intracellular distribution of biothiols within living HeLa cells. Furthermore, our studies with human blood plasma demonstrated the possibility of using this reagent for the quantitative optical detection of total biothiols in biological fluid. Such an example for the detection of biothiols in real biological samples is rare in the contemporary literature. These results clearly demonstrate the possibility of using this reagent in medicinal biology and diagnostic applications.